Inertial proximal point regularization algorithm for unconstrained vector convex optimization problems - Nguyen Buong (Український математичний журнал, 2008)
The purpose of the paper is to investigate an iterative regularization method of proximal point type for solving ill-posed vector convex optimization problems in Hilbert spaces. The application to the convex feasibility problems and the common fixed points for nonexpansive potential mappings is also given.